A local energy management of a hybrid PV-storage based distributed generation for microgrids. (15th January 2015) - Choudar, Adel; Boukhetala, Djamel; Barkat, Said; Brucker, Jean-Michel
Highlights: The proposed system is based on photovoltaic system, batteries and ultra-capacitors. Batteries are used as an energy source, ultra-capacitors are used as a fast power regulator. An energy management strategy, to operate a grid connected active PV system (APS). Different levels of the control system are studied and organized in a hierarchical control structure. Different operating modes are explained (island, limited PV power, normal, fast recovering). Abstract: The presented work focuses on energy management strategy, to operate a grid connected active PV system ( APS ) in a microgrid. A microgrid is a smart grid in a small scale which can be stand-alone or grid-tied. The proposed system is based on photovoltaic system, batteries and ultra-capacitors. Three converters are used to interface the elements of the APS to a common DC-link capacitor. The presented control strategy manages the power flow between the converters and the grid through the DC-link in order to maintain the grid power demand coming from the grid operator. Batteries are used as an energy source, to stabilize and permit the APS units to run at a constant and stable output power, damping peak surges in electricity demand and to store the excess of energy from the PV array. Ultra-capacitors are used as a fast power regulator to: limit the battery's current, regulate the DC-link voltage when the disconnection mode occurs and to deliver a smooth power to the grid, despite primary source and load fluctuations. Several operating modes are presented to manage locally the power flows between the various sources, taking into account the state of charge of batteries ( SOC ), the energy level of ultra-capacitors ( Lev ), the available PV power and the power demand from the grid operator.